2013
DOI: 10.1017/thg.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Twin Births in Southeast China: 1993–2005

Abstract: Recently, there has been a significant increase in the rate of multiple births in most developed countries. However, few population-based studies have been conducted in China regarding the epidemiology of twin births in recent years. We performed a descriptive analysis of twin births from 1993 to 2005 using data from a population-based perinatal care program in southeast China. The twin birth rate in southeast China was 0.65%, and the twin birth rates from 1993 to 2005 fluctuated between 0.60% and 0.70%. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…We found that the overall twinning rate of 18.8‰ was similar to previous rates observed in China (from 13 to 20.5 per 1000 births) [2224] and other Asian countries (i.e. 19.3‰ in 2002 in Korea [25] and 19.5‰ in 2009 in Japan [26]) but lower than those in some western countries (i.e., 27.3‰ in England and Wales, 28.3‰ in France in 1997 [6], and 33.3‰ in 2009 in the United States [1]).…”
Section: Discussionsupporting
confidence: 86%
“…We found that the overall twinning rate of 18.8‰ was similar to previous rates observed in China (from 13 to 20.5 per 1000 births) [2224] and other Asian countries (i.e. 19.3‰ in 2002 in Korea [25] and 19.5‰ in 2009 in Japan [26]) but lower than those in some western countries (i.e., 27.3‰ in England and Wales, 28.3‰ in France in 1997 [6], and 33.3‰ in 2009 in the United States [1]).…”
Section: Discussionsupporting
confidence: 86%
“…Data collection and all methods used in the surveillance program were approved by the institutional review board of Peking University Health Science Center. Oral informed consent was obtained from every woman as per the PHCSS protocol [ 28 , 29 ]. Women residing in regions covered by the PHCSS registered at their marital physical examination or first prenatal visit.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence of multiple birth in China is rising [ 15 ], but no recent studies have examined pregnancy complications in women with multiple pregnancy using a multi-center database. The two-child policy was established in China in 2016, so a baby-boom period is expected in the next decade and, with it, an increase in multiple gestation pregnancies.…”
Section: Introductionmentioning
confidence: 99%